Outcome of focused training on tuberculosis and air-borne infection control for third-year undergraduate medical students - Ubale, Milind; Ubale, Sunita; Malgaonkar, Aniruddha Arjun; Kartikeyan, Sundaram (International Journal of Research in Medical Sciences, 2016)
Background: Though health care personnel are at particularly high risk of contracting air-borne infections, including tuberculosis, the current undergraduate health science curriculum does not have a course devoted to training on airborne infection control and universal biosafety precautions in the pre-clinical stage. Methods: This before-and-after type of educational interventional study (without controls) was conducted on third-year medical students (n=55) in state of Maharashtra, Western India. After completing curriculum-based traditional didactic lectures on tuberculosis and air-borne infection control, a pre-test was conducted. After focused training on tuberculosis and air-borne infection control the post-test was administered. The outcome studied was the difference in cognitive domain scores after attending traditional didactic lectures (by a pre-test) and focused training (by a post-test). Results: The differences between correct responses in pre-and post-tests were statistically significant in 12 out of 15 questions with an overall increase in median correct responses in the post-test with increase in minimum and first quartile. Conclusions: The study results reflect the superiority of focused training using videos and practical demonstration over traditional didactic lectures. This study highlights the focus areas in teaching infection control measures and the importance of focused training in the curriculum for undergraduate medical students. It is necessary to review the curriculum so that knowledge on infection prevention and control is imparted during the pre-clinical first year before medical students enter clinical settings.